2021
DOI: 10.46661/ijeri.5766
|View full text |Cite
|
Sign up to set email alerts
|

Physical Education and Sports Lesson in Distance Education: Content Analysis of Videos on Youtube

Abstract: In this study, it was aimed to examine how physical education and sports teachers taught lessons in the distance education process and which activities they included in the course content during the Covid 19 pandemic process. The videos published under the title of distance education physical education and sports lessons written in Turkish on YouTube were analyzed. The videos were analyzed using content analysis technique. Three themes were obtained as a result of the content analysis. These are the themes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Again, social networking sites are seen by educators as the Web 2.0 application that will provide the most benefit to student interaction (Ajjan & Harsthone, 2008). Among these social networking sites, the Youtube platform is used in a wide range of educational fields, from medicine to sports, from mathematics to science (Del Valle-Ramón et al, 2020;Gayef & Çaylan, 2021;Pecay, 2017;Yücekaya et al, 2021). It was found that students in the study group mostly used the Youtube platform to improve their instrumental playing skills.…”
Section: Discussionmentioning
confidence: 99%
“…Again, social networking sites are seen by educators as the Web 2.0 application that will provide the most benefit to student interaction (Ajjan & Harsthone, 2008). Among these social networking sites, the Youtube platform is used in a wide range of educational fields, from medicine to sports, from mathematics to science (Del Valle-Ramón et al, 2020;Gayef & Çaylan, 2021;Pecay, 2017;Yücekaya et al, 2021). It was found that students in the study group mostly used the Youtube platform to improve their instrumental playing skills.…”
Section: Discussionmentioning
confidence: 99%
“…YouTube's extensive reach and engagement ability make it the ideal technology for serving as a complementary learning channel, extending the classroom environment beyond university walls and into natural physical activity settings [33] . When students access YouTube seeking support in motor and procedural learning, they enjoy the compatibility of their procedural learning strategies with the features that YouTube provides [34] , the enormous amount of relevant, up-to-date learning contents [35] , the sense of vividness and creativity imposed by the available instructional videos [36] , as well as the sense of self-efficacy while learning skills and acquiring knowledge [37] .…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence showing that YouTube, when properly incorporated into formal educational settings, can effectively complement daily curriculum delivery [ 32 , 34 , 38 , 39 ]. This provides support to the self-reports of sports science students who took part in this study, perceiving YouTube as a valuable complementary learning resource in times of COVID-19.…”
Section: Recommendationsmentioning
confidence: 99%
“…The implementation of learning that can utilize or be integrated with computers will increase student interest in learning and academic achievement (Junaidi, 2019;Kumar & Hema, 2017). This allows the realization of an innovation in the implementation of distance running athletic learning based on ICT-based learning media which can also be applied or run on smartphones (Akkaya, 2021;Sağin, 2021). This learning media will be a means or learning aid that is more effective in delivering material and efficient in the use of time and energy (Lim et al, 2020;Roemintoyo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%